DEVELOPMENT OF COMPACT LASER GLUCOMETER FOR DIABETES SCREENING AND MONITORING - Mohd Nurul Iman, Mohd Fouzi (Universiti Malaysia Sarawak (UNIMAS), 2020)
Diabetes is a metabolic disease that caused by high glucose level in the human bloods. Diabetes disease if not monitored very well will lead to serious health problems such as end-stage renal disease, amputation of the lower limbs, blindness, and cardiovascular disease. In current development in medical research, there are three different method used to monitor glucose concentration in blood. This method known as invasive, minimally invasive and non-invasive. This research is more focus on non-invasive method which the glucose concentration reading in blood obtained without contact or break to the human skin. Usually, glucometer was used to get the glucose reading from the blood obtained thru finger-prick process. However, this may cause irreparable tissue damage and therefore is not favorable for continuous monitoring of glucose. There is risk on getting an infection, due to finger-prick causing a break to human skin. Besides, many non-invasive blood glucose measurement techniques are still in medical research and clinical studies. Therefore, it is imperative to develop compact laser glucometer with capability to measure the glucose concentration from the human urine by manipulating the optical light refraction which known as Snell’s law theory. The compact laser glucometer was initially designed using a CAD software. This device laser holder was fabricated using a 3D printing while the base for entire device was machined using a multi-axis milling machine. Sugar syrup solution with different concentration was used for calibration purpose. Once calibration of compact laser glucometer using sugar syrup solution was done, the results analyzed using measurement software. To get better and clearer images of laser refraction in the sugar syrup solution, the calibration was conducted in the dark surrounding. Thereafter, an equation for the developed compact laser glucometer was obtained. The experiment was successfully demonstrated using developed compact laser glucometer on human urine samples. In order to improve the accuracy during calibration, scattering agent should be added to the sugar syrup solution it can provide a higher visibility of the refracted laser light in the solution.